The context of the creative society in leaders’ political speeches - Markauskaitė, Karolina (Creativity Studies, 2025)
This paper explores the context of the creative society in the political speeches of leaders. The study uses qualitative content analysis to analyse the speeches of political leaders and citizen leaders, how they recur and reflect themes relevant to the creative society. Citizen leaders in the context of this study are well-known and active public figures, public figures, leaders of various non-governmental organizations who speak out on issues of public interest. Political leaders are politicians who carry out political communication, which is focused on attracting voters, and their speeches are part of their image-building. The study showed that political leaders are more likely to give speeches, but citizen leaders are more likely to give speeches on topics of creative public interest, their speeches tend to focus on themes such as exceptionalism, they seek to touch the audience’s feelings, they talk about how everyone wants to feel important, to make a contribution to solving a problem, and they emphasise how we can each contribute to the destruction of hierarchy. Political leaders usually talk about economic growth – North Atlantic Treaty Organization, European Union – but also about human freedoms, how they were fought for in the past and how important it is now. The results of this research can help citizens and political leaders to improve their political communication, namely their languages, to understand what kind of communication is relevant for a creative society.